An Efficient Manifold Algorithm for Constructive Interference Based Constant Envelope Precoding - Fan Liu; Masouros, Christos; Amadori, Pierluigi Vito; Huafei Sun (IEEE signal processing letters, 2017)
In this letter, we propose a novel manifold-based algorithm to solve the constant envelope (CE) precoding problem with interference exploitation. For a given power budget, we design the precoded symbols subject to the CE constraints, such that the constructive effect of the multiuser interference is maximized. While the objective function for the original problem is not complex differentiable, we consider the smooth approximation of its real representation, and map it onto a Riemannian manifold. By using the Riemmanian conjugate gradient algorithm, a local minimizer can be efficiently found. The complexity of the algorithm is analytically derived in terms of floating-points operations (flops) per iteration. Simulations show that the proposed algorithm outperforms the conventional methods on both symbol error rate and computational complexity.